Implementasi Algoritma Round Robin Untuk Pengaturan Jam Kerja Karyawan PT. Fasih Timber - Sunardi; Eris Purnama; Mochammad Darip (BETRIK, 2026)
This study aims to implement the Round Robin algorithm to optimize employee working hours at PT Fasih Timber, a plywood manufacturing company. The main challenges faced are limited manpower in the mechanical department and shipping warehouse, as well as high overtime costs due to inefficient schedule management. The Round Robin algorithm is applied to ensure fair and flexible work distribution in the face of unexpected situations. The research method includes analyzing company needs through interviews, observations, and simulation of work data with software. The results of the study show that the implementation of the Round Robin algorithm can reduce overtime costs, increase time efficiency, and create a fairer work environment. This technology-based scheduling system also provides optimal schedule recommendations and supports digital transformation steps in companies with an efficiency value of 90%, effectiveness of 86%, and satisfaction of 80%. Thus, this approach can be an innovative solution for human resource management in the manufacturing industry sector.